Pemanfaatan Media Digital sebagai Sarana Dakwah Islam di Era Modern: Peluang, Tantangan, Strategi, dan Implikasi terhadap Pemahaman Keagamaan Masyarakat - Hilma Aulia; Elsa Zakiah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of information and communication technology has fundamentally transformed the way Islamic preaching (da’wah) is delivered in the digital era. This article examines the utilization of digital media as a strategic means of disseminating Islamic values in contemporary society, focusing on opportunities, challenges, ethical dimensions, and communicative implications of digital da’wah. The study employs a qualitative approach through a systematic literature review by synthesizing findings from scientific journals, mostly published within the last five years (2020–2025). The results indicate that digital platforms such as YouTube, Instagram, TikTok, and podcasts significantly expand the reach of Islamic preaching beyond spatial and temporal limitations, particularly among the younger generation. However, this development also presents challenges, including the proliferation of unverified religious content, the risk of provocative communication, and strong competition with more engaging entertainment content. Therefore, effective digital da’wah requires not only technical capability but also the integration of religious competence, digital literacy, and Islamic communication ethics to ensure that the message remains authentic, relevant, and responsible.